Cartilage repair of the knee joint Knorpelreparative Eingriffe am Kniegelenk - Rath, Björn; Eschweiler, J.; Gruber, G.; Betsch, Marcel (Orthopäde, 2017)
Background: Cartilage defects around the knee joint frequently occur in the region of the medial femoral condyle and the retropatellar cartilage surface. The distinction between local cartilage defects and large area degenerative cartilage lesions is very important for both prognosis and surgical therapy. The size and position of the lesion, the underlying pathomechanism and the age of the patient are very important factors which should be considered in the therapy algorithm for optimal cartilage defect restoration. Important cofactors such as stability, long leg axis and muscle balance should be taken into account. Aim: Current procedures for cartilage repair of the knee joint and their results are summarized in this article. In addition, the necessity of precise and comprehensive preoperative clinical and radiological diagnostics is displayed to be able to treat co-pathologies in order to enable a successful repair of the cartilage defect. Results and conclusions: Preoperative planning of cartilage-repair techniques usually includes x‑ray images and a magnetic resonance imaging (MRI) examination. If MRI is not available, an arthro-computed tomography could be an alternative. Modern and routinely used procedures for cartilage repair at the knee joint are microfracture, autologous matrix-induced chondrogenesis, autologous chondrocyte transplantation, matrix-induced autologous chondrocyte implantation and osteochondral transplantation. Successful surgical cartilage-repair surgeries require a correct and individualized indication, addressing of copathologies and a standardized rehabilitation that is adapted to the surgical procedure. Evidence-based criteria for an exact time point for the return to sports according to individually operative cartilage repair techniques currently do not exist.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Autologous chondrocyte transplantation; Autologous matrix-induced chondrogenesis; Medial femoral condyle; Microfracture; Patella